Modulation of Speech Motor Learning with Transcranial Direct Current Stimulation of the Inferior Parietal Lobe - Deroche, Mickael L. D.; Nguyen, Don L.; Gracco, Vincent L. (Frontiers in Integrative Neuroscience, 2017)
The inferior parietal lobe (IPL) is a region of the cortex believed to participate in speech motor learning. In this study, we investigated whether transcranial direct current stimulation (tDCS) of the IPL could influence the extent to which healthy adults 1) adapted to a sensory alteration of their own auditory feedback, and 2) changed their perceptual representation. Seventy subjects completed three tasks: a baseline perceptual task that located the phonetic boundary between the vowels /e/ and /a/; a sensorimotor adaptation task in which subjects produced the word “head” under conditions of altered or unaltered feedback; and a post-adaptation perceptual task identical to the first. Subjects were allocated to four groups which differed in current polarity and feedback manipulation. Subjects who received anodal tDCS to their IPL (i.e. presumably increasing cortical excitability) lowered their first formant frequency (F1) by 10% in opposition to the upward shift in F1 in their auditory feedback. Subjects who received the same stimulation with unaltered feedback did not change their production. Subjects who received cathodal tDCS to their IPL (i.e. presumably decreasing cortical excitability) showed a 5% adaptation to the F1 alteration similar to subjects who received sham tDCS. A subset of subjects returned a few days later to reiterate the same protocol but without tDCS, enabling assessment of any facilitatory effects of the previous tDCS. All subjects exhibited a 5% adaptation effect. In addition, across all subjects and for the two recording sessions, the phonetic boundary was shifted towards the vowel /e/ being repeated, consistently with the selective adaptation effect, but a correlation between perception and production suggested that anodal tDCS had enhanced this perceptual shift. In conclusion, we successfully demonstrated that anodal tDCS could 1) enhance the motor adaptation to a sensory alteration, and 2) potentially affect the perceptual representation of those sounds, but we failed to demonstrate the reverse effect with the cathodal configuration. Overall, tDCS of the left IPL can be used to enhance speech performance but only under conditions in which new or adaptive learning is required.